EXPLORATION OF THE HOMBO BATU TRADITION OF NIAS AS A STEM LEARNING MEDIA: INTEGRATION OF BIOLOGY, PHYSICS, AND MATHEMATICS - Darmawan Harefa (Universitas Nias Raya, 2025)
This study aims to explore the potential of the Hombo Batu tradition of Nias as a STEM learning medium integrating aspects of Biology, Physics, and Mathematics for junior high school students in South Nias. Hombo Batu, a traditional stone-jumping practice rich in local wisdom, serves as a real-life context for learning scientific concepts through direct experience. The research employed a qualitative approach with a case study design, involving observations, interviews with teachers and students, and analysis of learning documents. The findings indicate that integrating Hombo Batu into STEM learning significantly improves students’ understanding of physics concepts (force, energy, motion), biology (balance, muscle coordination, biomechanics), and mathematics (measurement of distance, angles, ratios). In addition, students demonstrated higher engagement, critical thinking skills, creativity, and collaboration compared to conventional learning methods. The tradition also strengthens students’ cultural appreciation and local identity, making learning more contextual and meaningful. However, successful implementation requires teacher readiness, adequate facilities, and involvement of the local community to ensure cultural accuracy. The study emphasizes that incorporating local wisdom as a STEM learning medium not only enhances scientific literacy but also fosters character development, creativity, and pride in one’s cultural heritage.